Fostering Intellectual Competence through Dialogic Learning in Islamic Boarding Schools - Fitriyanti, Windy Ana; Haryanto, Budi (Universitas Muhammadiyah Sidoarjo, 2024)
This qualitative case study investigates the development of intellectual competence through dialogic learning at an Islamic boarding school. Employing participatory observation, the study explores the process of fostering intellectual competence through discussions within and outside formal learning activities, encouraging critical thinking towards diverse viewpoints, promoting confident expression grounded in literature, and active participation in scientific competitions. Results demonstrate that dialogic learning enhances students' critical thinking skills and encourages active engagement in scholarly pursuits, both locally and nationally. This research underscores the significance of dialogic pedagogy in nurturing intellectual competence within Islamic educational contexts, offering implications for fostering critical thinking and scholarly engagement in diverse educational settings. Highlights : Dialogic learning fosters critical thinking: Encouraging discussions outside formal activities cultivates a critical attitude towards diverse opinions. Confidence in expression through literature: Instilling the courage to express opinions grounded in literature enhances intellectual competence. Active participation in scientific competitions: Engagement in local and national competitions promotes scholarly pursuits and intellectual growth. Keywords: Dialogic learning, Intellectual competence, Islamic boarding schools, Critical thinking, Scholarly engagement